Zirconium in the Nuclear Industry: Tenth International Symposium 1994
DOI: 10.1520/stp15192s
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Zr-2.5Nb Pressure Tubes to Minimize the Harmful Effects of Trace Elements

Abstract: Trace elements can reduce the fracture resistance of Zr-2.5Nb pressure tubes. The effects of hydrogen as hydrides and oxygen as an alloy-strengthening agent are well known, but the contributions of carbon, phosphorus, chlorine, and segregated oxygen have only recently been recognized. Carbides and phosphides are brittle particles, while chlorine segregates to form planes of weakness that produce fissures on the fracture face of test specimens. A high density of fissures is associated with low toughness. With l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Tubes made from Zr-2.5 wt% Nb alloy [1][2][3][4][5][6][7] in cold worked and stress-relieved (CWSR) condition, are called pressure tubes, which act as miniature pressure vessels in Pressurized Heavy Water Reactors (PHWR) and operate over the temperature range of 526-566 K under an internal pressure of $10.5 MPa, and neutron flux of the order of 3 · 10 17 n/m 2 /s. The initial hydrogen content of the pressure tubes is kept as low as possible by controlling the manufacturing process parameters [8]. However, part of the hydrogen/deuterium evolved during service from coolant-metal corrosion reaction is picked up by the pressure tubes of the PHWR.…”
Section: Introductionmentioning
confidence: 99%
“…Tubes made from Zr-2.5 wt% Nb alloy [1][2][3][4][5][6][7] in cold worked and stress-relieved (CWSR) condition, are called pressure tubes, which act as miniature pressure vessels in Pressurized Heavy Water Reactors (PHWR) and operate over the temperature range of 526-566 K under an internal pressure of $10.5 MPa, and neutron flux of the order of 3 · 10 17 n/m 2 /s. The initial hydrogen content of the pressure tubes is kept as low as possible by controlling the manufacturing process parameters [8]. However, part of the hydrogen/deuterium evolved during service from coolant-metal corrosion reaction is picked up by the pressure tubes of the PHWR.…”
Section: Introductionmentioning
confidence: 99%
“…Either due to garter spring displacement from the designed location or due to creep or both [8], the PT sags, and may contact the CT, resulting in setting-up of thermal gradient across the PT. Though the initial hydrogen content of the PT is kept as low as possible by controlling manufacturing process parameters [9], it can pick up hydrogen/deuterium during service [10]. Hydrogen is known to migrate down the concentration and temperature, and up the tensile stress gradient [11] in zirconium and its alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that pressure tubes manufactured from ingots of 100% recycled material (RM) have high toughness due to the elimination of particles including the Zr-Cl-C complex carbide, zirconium phosphide, and carbide [3][4][5]. The elimination of these particles reduces the number of void nucleation sites and improves the fracture toughness as shown in Figure 1.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…The CCL ranges from a minimum of ≈41 mm to a maximum of >80 mm. The minimum is from a burst test of a low toughness tube, which had a high concentration of harmful trace elements, Cl and P [5]. This tube was manufactured in the late 1960s and is not considered representative of modern production tubes.…”
Section: Fracture Toughnessmentioning
confidence: 99%
See 1 more Smart Citation